A Clinical Evaluation of Mifepristone as a Cervical Ripening Agent and Labour Inducer in Term Pregnancies - Chaudhary, Ruta; Desai, Dhruv; Pawar, Atul (International Journal of Innovative Research in Medical Science, 2025)
Background: To evaluate the efficacy of mifepristone in pre induction cervical ripening in term pregnancy. Materials and Methods: Prospective interventional randomised comparative study, done at Holy family hospital New Delhi. 100 patients were selected randomly with a bishop score less than 6. The study group included fifty patients who received 200 mg oral mifepristone (if applicable, repeat once after 24 hrs). The expectant group included 50 patients, whom we observed for 48hrs without interference. Comparison was done in terms of improvement in bishop score, need for further induction and augmentation of labour, induction to delivery interval and mode of delivery. Results: In the mifepristone group, there was a statistically significant difference in the number of PGE2 gel required with a p value of 0.0001. The study group demonstrated a significantly lower proportion of patients requiring further doses of PGE2 gel compared to the expectant group. The median PGE2 gel to delivery interval in the expectant group was 11.5hrs which was significantly higher compared to the study group, where the median interval was 8 hrs. In our study there was a statistically insignificant difference in the improvement in the bishop score with a p-value of 0.824, also in terms of complications and neonatal outcome. Conclusion: This study showed that oral mifepristone given for pre induction cervical ripening is an effective agent when given at least 24- 48 hrs prior in full term pregnancy.